Trans-border transactions in North East India : focus-Tripura-Bangladesh border - Ray, Ashok Kumar (New Delhi Aakar Books, 2020)
The book begins with a critique of the inter-relationship between community, state and market and then looks into the cross-border transactions in North-East India with special focus on the Tripura-Bangladesh border. It problematises the spatial identity of Tripura in pre and post-partition era and the implications of partition and border-making to the cross-border communities of Tripura and Bangladesh. It reflects on trade transactions between India and Bangladesh and more significantly, on informal cross-border trade, social transactions and people-to-people contact across the border. This book also captures the community anxieties emerging from land boundary institutions and the issues of conflict and development in the cross-border space of Tripura-Bangladesh. In conclusion the book captures the dynamics of community inter-dependence and opposition in the post-partition condition in the Tripura and Bangladesh. Asok Kumar Ray is a scholar on North East India. He has authored and co-edited several books and has written many research papers on North East India. He was a visiting fellow at OKDISCD, Guwahati.
Keywords: International relations; India--Tripura